2018
DOI: 10.3390/polym10010077
|View full text |Cite
|
Sign up to set email alerts
|

EBR Strengthening Technique for Concrete, Long-Term Behaviour and Historical Survey

Abstract: Epoxy bonded steel plates (externally bonded reinforcemen: EBR) for the strengthening of concrete structures were introduced to the construction industry in the late 1960s, and the use of fibre reinforced polymers (FRPs) was introduced in the 1990s, which means that these techniques have already been used in construction for 50 and 25 years, respectively. In the first part of the paper, a historical survey of the development and introduction of these strengthening techniques into the construction industry are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…-A feasible setup for on-site GA applications was developed in cooperation with the S&P Clever Reinforcement Company AG (Seewen, Switzerland) and Empa. -It has been demonstrated that environmental conditions, such as humidity, temperature and FT cycle can affect the performance of the GA and, in combination with high CFRP prestresses and/or high sustained loading, are critical for their long-term behavior. Therefore, similar recommendations such as the one proposed by (Czaderski and Meier, 2018) for unstressed CFRP can be applied to RC elements strengthened using the GA method. The most important are:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-A feasible setup for on-site GA applications was developed in cooperation with the S&P Clever Reinforcement Company AG (Seewen, Switzerland) and Empa. -It has been demonstrated that environmental conditions, such as humidity, temperature and FT cycle can affect the performance of the GA and, in combination with high CFRP prestresses and/or high sustained loading, are critical for their long-term behavior. Therefore, similar recommendations such as the one proposed by (Czaderski and Meier, 2018) for unstressed CFRP can be applied to RC elements strengthened using the GA method. The most important are:…”
Section: Discussionmentioning
confidence: 99%
“…The use of composite materials for structural strengthening is nowadays considered a practical and ordinary solution to increase load-carrying capacity and extend the life of reinforced concrete structures. As a result of more than two decades of international research and pioneering applications (Czaderski and Meier 2018), it is possible to deliver strengthening solutions based on the use of FRP with a good level of safety. The advantages are well known; composite materials used for structural strengthening, such as, for example, Carbon Fiber Reinforced Polymers (CFRP) have excellent mechanical properties, i.e., a high ultimate tensile strength and modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…A. CFRP patches: Externally bonded reinforcement (EBR) appeared in the 1980s [27]. In the last decades, fiber reinforced polymer (FRP) materials have been increasingly proposed to strengthen RC structures [28].…”
Section: Materials and Techniques Of The Rc Slab Retrofit Proposed Inmentioning
confidence: 99%
“…Strengthening of the deteriorated structures, using externally bonded reinforcement (EBR) materials became one of the most widely used strengthening methods as given by several comprehensive reviews and surveys [ 1 , 2 , 3 , 4 , 5 , 6 ]. During the last three decades, carbon fiber reinforced polymer (CFRP) composites have become the material of choice that has been used widely for flexure and shear strengthening in the construction industry.…”
Section: Introductionmentioning
confidence: 99%